Enhancing diagnostic sensitivity: Investigating molecular mechanisms of Antigen Rapid Diagnostic Test (AgRDTs) variability across SARS-CoV-2 variants - Frank Twum Aboagye; Mawutor Kwame Ahiabu; Maame Ekua Acquah; Queenstar Quarshie; Naa Kumah; Hannah Akahoho; Nfayem Imoro; Abena Enninful; Bill Egyam; Yvonne Ashong (Research Ideas and Outcomes, 2025)
The emergence of COVID-19, caused by SARS-CoV-2, led to the widespread use of antigen rapid diagnostic tests (AgRDTs) due to their speed, affordability and ease of use. However, the diagnostic sensitivity of AgRDTs has been inconsistent across emerging SARS-CoV-2 variants, with some variants exhibiting reduced detection rates. Thus, AgRDTs have been unreliable in detecting the different variants of SARS-CoV-2. This study explores the molecular mechanisms responsible for this variability, focusing on structural changes in the viral spike (S) and nucleocapsid (N) proteins and how these changes affect antigen-antibody interactions. Using structural biology techniques, such as X-ray crystallography and cryo-electron microscopy, molecular virology approaches like whole genome sequencing, immunoassays including ELISA and surface plasmon resonance (SPR) and computational modelling tools for molecular dynamics simulations, this research will uncover specific mutations that impact diagnostic sensitivity. The results of this study will provide information for the development of next-generation AgRDTs with enhanced sensitivity across diverse viral variants, thereby supporting global efforts in pandemic surveillance and control.